From nonrenewable to renewable energy and its impact on economic growth: The role of research & development expenditures in Asia-Pacific Economic Cooperation countries. (1st March 2019) - Zafar, Muhammad Wasif; Shahbaz, Muhammad; Hou, Fujun; Sinha, Avik
Abstract: This study disaggregates energy, i.e. non-renewable and renewable energy consumption, and investigates its effect on economic growth. The period of 1990–2015 is used to examine Asia-Pacific Economic Cooperation (APEC) countries. This paper determines the cross-sectional dependence and employs a second-generation panel unit root test for precise estimation. Westerlund cointegration test is used to examine the long-run equilibrium relationship between the variables and confirm the presence of cointegration in the long run. The Continuously Updated Fully Modified Ordinary Least Square (CUP-FM) approaches are applied to investigate long-term output elasticities between the variables. The results show the stimulating role of energy (renewable and nonrenewable) consumption in economic growth. Research and development expenditures and trade openness have a positive effect on economic growth. Moreover, the time series individual country analysis also confirms that renewable energy has a positive impact on economic growth. The heterogenous causality analysis reveals the feedback effect, i.e., bidirectional causal associations among economic growth, renewable energy consumption, and nonrenewable energy consumption. This empirical evidence suggests that countries should increase investment in renewable energy sectors and plan for development in renewable energy for sustainable energy growth. Graphical abstract: Highlights: We analyze the growth-energy-capital-trade-R&D expenditures association. Study is done for 16 in Asia-Pacific Economic Cooperation (APEC) countries during the period of 1990–2015. Long-run output elasticities are estimated for panel and individual countries. Energy consumption in any form increases economic growth. Research and Development expenditure increases economic growth.